An oversimplification of physiological principles leads to flawed macroecological analyses. Issue 21 (21st October 2019) - Boyles, Justin G.; Levesque, Danielle L.; Nowack, Julia; Wojciechowski, Michał S.; Stawski, Clare; Fuller, Andrea; Smit, Ben; Tattersall, Glenn J.
Abstract : Macrophysiological analyses are useful to predict current and future range limits and improve our understanding of endotherm macroecology, but such analyses too often rely on oversimplifications of endothermic thermoregulatory and energetic physiology, which lessens their applicability. We detail some of the major issues with macrophysiological analyses based on the classic Scholander–Irving model of endotherm energetics in the hope that it will encourage other research teams to more appropriately integrate physiology into macroecological analyses.